Modern Socio-Economic Conditions in the Formation of Small Towns in the Fergana Region (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article studies the development of small towns and settlements in the Fergana region, analyzing the socio-economic, geographical and environmental factors affecting urbanization. By studying the processes of agglomeration, it is revealed that they are monocentric and polycentric.